Sustainable diets and risk of overweight and obesity: a systematic review and meta-analysis - Reger, Christoph; Leitzmann, Michael F.; Rohrmann, Sabine; Kühn, Tilman; Sedlmeier, Anja M.; Jochem, Carmen (Obesity reviews, 2024)
Sustainable diets are gaining interest as a possible approach to tackle climate change and the global extent of obesity. Yet, the association between sustainable diets and adiposity remains unclear. We performed a systematic review and meta-analysis, calculating summary relative risks and 95% confidence intervals (CI). We pooled maximally adjusted risk estimates, assessed heterogeneity and publication bias, calculated the E-value, and evaluated the risk of bias across the included studies. A total of eight studies were eligible for analysis. Comparing the highest versus the lowest levels of adherence to sustainable diets, the pooled effect estimate was 0.69 (95% CI = 0.62-0.76) for overweight and 0.61 (95% CI = 0.47-0.78) for obesity. These results suggest that sustainable diets may decrease the risk of overweight/obesity and therefore could serve as enablers for improving both public and planetary health. An agreed-upon clear definition of sustainable diets would enhance the comparability of future studies in this area.
Veröffentlicht: 11 February 2024
Gesehen am 20.06.2024